Analytical HPLC-separation of retinoid derivatives of natural and 3,4-didehydro series - N. E. Belikov; A. A. Khodonov; O. V. Demina; M. A. Yakovleva; T. B. Feldman; M. A. Ostrovsky (Тонкие химические технологии, 2014)
The goal of the present study was the development of composition analysis method for vision pigments chromophore groups of different animals with the use of high performance liquid chromatography as well as the development of synthetic method for all-E-3,4-didehydroretinal – one of standard compounds. The all-E-3,4- didehydroretinal synthetic route developed earlier has been polished, and the product structure has been confirmed by physical-chemical analysis methods. The chromatographic separation process of Z-isomers of natural retinal and 3,4-didehydroretinal has been studied under isocratic flow conditions with the use of one and two sequentially connected normal phase columns. Optimal chromatographic conditions have been proposed for the separation and analysis of both retinoid model mixtures and animal eye extracts.